Persistence of Diarrheal Pathogens Is Associated with Continued Recruitment of Plasmablasts in the Circulation. (19th January 2012) - Kantele, Anu
Abstract : Intestinal antigen encounter leads to recirculation of antigen-specific plasmablasts via lymphatics and blood back to the intestine. Investigating these gut-originating cells in blood provides a less invasive tool for studying intestinal immune responses, with the limitation that the cells disappear from the circulation in two weeks. No data exist on situations where pathogens persist in the intestine. Patients with Salmonella, Yersinia, or Campylobacter gastroenteritis and volunteers receiving an oral typhoid vaccine were assayed for plasmablasts specific to each subject's own pathogen/antigen weekly until the response faded. In vaccinees, plasmablasts disappeared in two weeks. In gastroenteritis, the response faded 2-3 and 3–7 weeks after the last positive Salmonella or Yersinia stool culture. Even in symptomless patients, pathogens persisting in the intestine keep seeding plasmablasts into the circulation. Assaying these cells might offer a powerful tool for research into diseases in which persisting microbes have a potential pathogenetic significance.